Jalb Masalih Izzuddin dan Relevansinya dengan Fatwa NU Terkait Shalat Jumat Masa Pandemi Covid-19 - Mushodiq, Muhamad Agus; Ghofur, Abdul; Mukhlishin, Ahmad; Santoso, Haris; Thohir, Muhyidin (Institut Agama Islam Negeri Curup, 2021)
This paper aims to explore Izzuddin’s jalb masalih concept and its relevance to the NU’s fatwa related to Friday Prayers during the Covid-19 pandemic. The authors use qualitative research with content analysis. The results of this study are. First. Izzuddin’s maqasid syari'ah leads to jalb masalih which also includes the concept of dzar'u mafasid. Second, Izzuddin integrates imanyah and ilmiyyah in the basic aspects of jalb masalih argumentation. Third, Izzuddin uses the two terms dzarury-hajiy-takmiliy and aliyat-mutawasitat-daniyat as levels of masalih and mafasid. The level of maslahah is influenced by differences in place and time. Fourth, dalil syara is used as the basis of the maqasid of the hereafter and logic, dzan, experiment, and habit as the basis of the maqasid of the world life. Fifth, the authors see the relevance between the results of the NU’s fatwa related to Friday Prayers during the Covid-19 pandemic and the concept of the jalb masalih conceptualized by Izzuddin ibn Abd Salam. The author's criticism is on the information about worship in the yellow zone where there should be a firmness in allowing Friday Prayers to comply with legal health protocols that are carried out based on WHO health recommendations and the rules of Izzuddin’s maqasid, Seventh, there needs to be a basis for differences in worship based on zone quality in the fatwa of Friday prayer. The conclusion obtained is the need for the adjustment of the NU Fatwa with the paguyuban Indonesian culture